ON REPRESENTING FACTORS INFLUENCING TIME PERFORMANCE OF SHOP-HOUSE CONSTRUCTIONS IN SURABAYA - Andi Andi; Susandi Susandi; Hendra Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2003)
Some shop-houses were built late and others are on time, or faster than the schedule that had been planned. The questions are how it could happen and what kind of factors that made it happened. This research has an objective to investigate time performance of shop-house constructions in Surabaya by representing factors that influence it. It first assembles potential influencing factors through literature review, and second, conducts an empirical study by collecting data from finished thirty-two shop-house projects throughout the city. Results of analyses using one-way analysis of variance (ANOVA) indicate eight factors to be statistically significant influencing time performance. They are construction design change, schedule of work that will be done, workers discipline, material availability, owner’s payment, quality control, workers availability, and material delivery. The paper discusses the factors and proposes possible solutions to improve time performance.